Providing Education about HIV/AIDS in Smks. Santo Yosef Nazaret Jayapura District - Hasnia, Hasnia; Lestari, Susi; Pratimi, Yustika Rahmawati; Lestari, Tiyan Febriani; Narianti, Narianti (Universitas Malahayati Lampung, 2024)
ABSTRACT The lack of appropriate and relevant information about HIV/AIDS and supported by the curious attitude of teenagers causes teenagers to be one of the populations with high risk behavior. Apart from that, the problem of HIV/AIDS in adolescents does not only have a negative physical impact, but can also affect mental health, emotions, economic conditions and social welfare in the long term. This not only affects teenagers themselves, but also families, society and the nation so that knowledge and attitudes have an important role in shaping behavior in preventing HIV/AIDS. However, in this case it is necessary to provide information in the form of education to increase knowledge and improve their own attitudes. The method used in this service so that students can be interested and absorb the education provided more quickly is providing education through audio-visual media (video) and print media (leaflets). Health education using videos and leaflets has a more significant impact on increasing knowledge because teenagers will be more interested in videos and leaflets, making teenagers less bored of watching and reading. Keywords: Education about HIV/AIDS, Knowledge and attitudes of female students, HIV/AIDS Videos and Leaflets, SMKS. Santo Yosef Nazareth, Jayapura Regency.